New Perspectives on Educational Resources Learning Materials Beyond the Traditional Classroom - Alvestad, Karl Christian; Nordberg, Kari H.; Roll-Hansen, Hege (Routledge Research in Education, 2024)
Bringing new perspectives on educational resources together, this book considers how a range of learning materials can be used to effectively highlight creativity, collaboration, and critical thinking in learning. Covering a broad scope of educational resources, the book examines the use of resources in Scandinavian education within language studies, literature, history, and social studies at all levels of education through empirically grounded research, including ethnographies and textual analysis. Written by practising experts in the field of education studies, chapters present examples of both cutting-edge digital media and more traditional artefacts and books, providing critical discussion and inspiration for how a range of resources can be used creatively within the classroom. This interdisciplinary book is a valuable addition to scholarly discussions around educational development and learning, and will be relevant for academics, researchers, and postgraduate students in the fields of teacher education, didactics, curriculum, and educational technology.